UJI IMUNOSTIMULATOR DARI KOMBINASI EKSTRAK ETANOL HERBA BINARA (ARTEMISIA VULGARIS LINN) DAN EKSTRAK ETANOL DAUN PUCUK MERAH (SYZYGIUM OLEANA) DENGAN METODE HIPERSENSITIVITAS TIPE LAMBAT PADA TIKUS - Romauli Anna Teresia Marbun; Aminah Syarifuddin; Montysory Silalahi; Radika Bella Fista Ginting (Jurnal Penelitian Farmasi & Herbal, 2019)
One of the herbs used is herbal binara (Artemisia vulgaris L) which has been studied as a potential immunomodulator with high antioxidant activity. Previous research also stated that red shoots (Syzygium oleana) were studied as potential immunomodulators with high antioxidant activity. Several other species such as Syzygium samarangense have 16 flavonoida compounds which show pharmacological immunological activity. The purpose of this study was to determine the content of secondary metabolites of ethanol extract of herbal binara (Artemisia vulgaris L.) with red shoots (Syzygium oleana) and to determine the best dose of extract from the ethanol extract of herbal binara (Artemisia vulgaris L.) with red shoots (Syzygium oleana) can reduce the volume of swelling of mouse feet. Examination of the chemical content of secondary metabolites from the ethanol extract of herbal binara (Artemisia vulgaris L.) with red shoots (Syzygium oleana) is carried out by chemical screening and characterization of simplicia and extract. The method used is the slow type hypersensitivity method. In this test the independent variable is the secondary metabolite of ethanol extract of herb binara (Artemisia vulgaris L.) with red shoots (Syzygium oleana) with four concentrations (50, 100, 200 and 400 mg / kgBB). The positive control used by Stimuno dose is 32.5 mg / kgBB.